2014
DOI: 10.1158/1055-9965.epi-14-0263
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Biomarker C-Reactive Protein and Radiotherapy-Induced Early Adverse Skin Reactions in Patients with Breast Cancer

Abstract: Background Breast cancer is the most frequently diagnosed cancer and the second leading cause of cancer death in American women. Post-surgery adjuvant radiotherapy (RT) significantly reduced the local recurrence rate. However, many patients develop early adverse skin reactions (EASRs) that impact quality of life and treatment outcomes. Methods We evaluated an inflammatory biomarker, C-reactive protein (CRP) in predicting RT-induced EASRs in 159 breast cancer patients undergoing RT. In each patient, we measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…Our prospective analysis also includes collection of genomic DNA, serum, and urine specimens at the start and completion of RT, and we are optimistic that future studies may begin to elucidate molecular and genetic mechanisms . Indeed, our preliminary analysis has uncovered a relationship between C‐reactive protein and skin reaction . However, the relationships identified in this study must be interpreted cautiously, and are simply hypothesis‐generating at this time.…”
Section: Discussionmentioning
confidence: 90%
“…Our prospective analysis also includes collection of genomic DNA, serum, and urine specimens at the start and completion of RT, and we are optimistic that future studies may begin to elucidate molecular and genetic mechanisms . Indeed, our preliminary analysis has uncovered a relationship between C‐reactive protein and skin reaction . However, the relationships identified in this study must be interpreted cautiously, and are simply hypothesis‐generating at this time.…”
Section: Discussionmentioning
confidence: 90%
“…Among the 11 comorbid conditions, diabetes, hypertension, or thyroid disease may increase pain intensity through modulating pain hypersensitivity/threshold, systemic inflammation, and/or radio-sensitivity [44]. Our previous study demonstrated that comorbid conditions increased inflammatory biomarker in radio-sensitivity and skin toxicity, particularly among obese breast cancer patients [35]. These comorbid conditions will need to be considered as part of the treatment decision making process and effective pain management strategies are needed to improve QOL in high-risk breast cancer patients with at least 2 comorbid conditions.…”
Section: Discussionmentioning
confidence: 99%
“…High-sensitivity CRP Acute phase protein synthesized during an inflammatory response; has been evaluated in head and neck cancers undergoing RT; maybe an indicator of persistent cardiac inflammation secondary to RT and ongoing remodeling; elevated CRP is predictive of decreased LVEF and diastolic dysfunction. 43…”
Section: Myeloperoxidasementioning
confidence: 99%